Bacterial Surface Displaying L-Glutamate Oxidase and Its Application on MSG Analysis - Yulian Ellyastono, Edwin
Monosodium glutamate (MSG) is a food additive which is used as a flavor enhancer. The global consumption of MSG was around 3.2 million tons in 2014 and increasing each year. Since it has a low toxicity level, the U.S. Food and Drug Administration (FDA) classified MSG as Generally Recognized as Safe (GRAS). However MSG consumption may cause several symptoms which is known as Chinese Restaurant Syndrome (CRS). Moreover, other reports showed that MSG consumption could increase blood pressure and obesity risk, induce oxidative stress up to the damage of nervous systems. Hence it is necessary to develop a simple, rapid and low cost analytical tool for MSG measurement. MSG analysis can be done by spectrophotometry, chromatography and biosensor methods. Among these methods, L-glutamate oxidase (GLOD) enzyme based biosensor has advantages in terms of simplicity, rapidness and relatively low cost. The drawbacks of enzyme based biosensor are time consuming and expensive purification. Therefore bacterial surface display was chosen to eliminate the purification step via presenting GLOD enzyme on the surface of Escherichia coli using N-terminal domain of Ice Nucleation Protein (NINP) variant InaZ. Based on these information, this study focus on the development of MSG biosensor based on whole cell E. coli displaying GLOD enzyme on its outer membrane. In order to fulfill the goal, GLOD gene without sequence encoding putative signal peptide (tGLOD) was fused with NINP gene and inserted into pET15b expression vector. The PCR colony, restriction enzyme analysis and DNA sequencing results showed that pET15b-NINP-tGLOD expression vector had been constructed. The SDS PAGE and activity assay results showed that fusion protein NINP-tGLOD was expressed in an active form and predicted to be displayed on the surface of E. coli with a molecular weight of estimated 88 kDa. The highest displayed GLOD enzyme activity was obtained at 37?C and pH 8 using Tris-Cl buffer. Moreover, displayed GLOD enzyme was able to maintain its 50% activity until 50?C. The development of MSG biosensor based on E. coli displayed GLOD enzyme was showed oxidation peak response at +0,35 V on cyclic voltammetry test. Based on these results, GLOD enzyme is predicted to be displayed on E. coli surface using NINP, premising further potential in the MSG biosensor development.